THE DEVELOPMENT OF TEACHERS’ LEARNING MANAGEMENT COMPETENCY USING TO LEARNING COMMUNITY PROFESSIONAL FOR ANUBAN TESABANMEUNG ROI-ET SCHOOL - Tothom, Chananthida (Academic Journal of Mahamakut Buddhist University Roi Et Campus, 2023)
The objectives of this research are to 1) study the current condition problems and needs in development teachers’ learning management competency using professional learning community for Anuban Tesabanmeung Roi-et School. 2) Create a model for development of teachers’ learning management competency using to learning community Professional for Anuban Tesabanmeung Roi-et School. 3) Experiment with a model for development teachers’ learning management competency using professional learning community for Anuban Tesabanmeung Roi-et School. It is characterized by research and development. The target group for development are 26 teachers of Anuban Tesabanmeung Roi-et School, 9 experts in group discussions to consider formats. The research tools include a questionnaire on current conditions, problems, and needs for development learning management competency. Group discussion recording form, Model Appropriate Assessment Form A knowledge and understanding test for learning management Learning Management Ability Evaluation Form Satisfaction questionnaire and manual for using the format Data were analyzed using statistics, mean, percentage, and standard deviation. The qualitative data were analyzed by content analysis. The research results: 1. the current conditions and competencies of teachers’ learning management for Anuban Tesabanmeung Roi-et School. Overall, it is of medium quality. 2. Model for developing teachers’ learning management competencies using professional learning communities for Anuban Tesabanmeung Roi-et School. The development has three components as follows. Part 1: Teachers’ learning management competencies using professional learning communities for Anuban Tesabanmeung Roi-et School. Part 2: Components of the model for development teachers’ learning management competencies using professional learning communities for Anuban Tesabanmeung Roi-et School. Part 3: The development process. Results of the inspection, evaluating the suitability and feasibility of the model for developing teachers’ learning management competencies for Anuban Tesabanmeung Roi-et School. The experts found that there was a high level of appropriateness and a high level of feasibility. 3. The results of the trial and evaluation of the use of the model for development teachers’ learning management competencies using professional learning communities for Anuban Tesabanmeung Roi-et School found that 1) Teachers’ knowledge and understanding of learning management after using the model is higher than before using the model. The difference is significant at the .05 level. 2) The ability of teachers to manage learning Overall, it is at the highest level. When considering each aspect, it was found that it was at the highest level in every aspect. 3) Teachers’ satisfaction with the development process according to the model for development teacher learning management competency for Anuban Tesabanmeung Roi-et School. Overall, it is at the highest level.